Raman Microspectroscopy of the Yeast Vacuoles - Bednárová, Lucie; Palacký, Jan; Bauerová, Václava; Hrušková-Heidingsfeldová, Olga; Pichová, Iva; Mojzeš, Peter (Spectroscopy: An International Journal, 2012)
In the present work, real ability of a confocal Raman microspectroscopy to monitor chemical composition of the vacuoles within living yeast cells was investigated and critically assessed. Simple, economical, and practical protocols of the yeast immobilization suitable for less laborious, high-throughput, and spatially resolved Raman measurements were tested for their possible impacts on physiological states and viability of the cells. We have demonstrated that, acquiring Raman spectra from statistically sound sets of immobilized cells and employing advanced multivariate methods for spectral analysis, the chemical composition of the yeast vacuoles can be reliably studied. The most easily and accurately quantifiable seems to be the concentration of polyphosphates which can be unambiguously identified due to unmistakable Raman features. Our approach can be useful for routine, label-free, and noninvasive monitoring of the chemical composition of the vacuoles of living yeasts exposed to various stress factors, the information important in biomedical research of pathogens.